Revolutionizing Waste Management: The Garbage Bank Solution and Its IT-Driven Implementation for Eco-Friendly Hygiene - Kaesar Azra Putra Zeva; MS Hasibuan; Firmansyah Firmansyah; Sutedi Sutedi (LPPM Universitas Islam 45 Bekasi, 2023)
The high yield of domestic household waste is a significant problem for environmental hygiene, where waste management is still not a top priority to provide profit opportunities for the community and the government. Thus, to campaign for ecological hygiene solutions by applying information technology in the form of a Garbage Bank, which can help deal with domestic waste, especially plastic waste. The Waste bank application is built using the CodeIgniter framework, which has the concept of Model, View, Controller (MVC), which has functions such as a model for the database framework, views of the system view and controllers as actions for executing user commands. The system was also developed using the extreme programming method with the advantage of being fast in development, simple and object-oriented. The resulting system has conducted a feasibility test to conclude that it is following its function. This research resulted in a system of three parts: the admin section, which can manage data on partners, customers, pick-ups to withdraw funds and reports. The partner section manages customer data, waste, pick-up and reports, and the customer section registers, views the history of saving waste, withdraws funds, and views types of waste and partners entirely done online.